17th IEEE International Conference on Micro Electro Mechanical Systems. Maastricht MEMS 2004 Technical Digest
DOI: 10.1109/mems.2004.1290676
|View full text |Cite
|
Sign up to set email alerts
|

A novel fabrication process of 3-D microstructures by double exposure in standard deep X-ray lithography

Abstract: This paper reports a novel fabrication process of 3 dimensional (3-D) microstructures by double X-ray exposure in standard deep X-ray lithography (DXL). The proposed fabrication process made it possible to realize 3-D microstructures with an inclined and curved sidewall without any apparatuses and difficult process control. In order to demonstrate the feasibility of the double X-ray exposure technique, a micro-needle array fabrication was carried out. The sharp micro-needle array with the top radius of less th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…A method to overcome the limitation in feature height is the use of X-ray lithography and pursue inclined exposure leading to needle-type shapes as it has been shown, for example, by Turner et al [20] using SU-8 and Matsuzuka et al [21], who were using polymethyl methacrylate. Again, hollow structures suitable for microfluidic conduits within a sharp tip were not yet demonstrated by these authors.…”
Section: High Aspect-ratio Polymer Fabricationmentioning
confidence: 99%
“…A method to overcome the limitation in feature height is the use of X-ray lithography and pursue inclined exposure leading to needle-type shapes as it has been shown, for example, by Turner et al [20] using SU-8 and Matsuzuka et al [21], who were using polymethyl methacrylate. Again, hollow structures suitable for microfluidic conduits within a sharp tip were not yet demonstrated by these authors.…”
Section: High Aspect-ratio Polymer Fabricationmentioning
confidence: 99%
“…A variety of three-dimensional (3-D) processing technologies, such as KOH anisotropic etching of silicon and laser machining [1], have been employed for the fabrication of microelectromechanical systems (MEMS). Previously, some research on 3-D processing methods using X-ray lithography with synchrotron radiation (SR) has been reported [2][3][4][5]. All these methods depend on the distribution of the exposure energy on the resist surface.…”
Section: Introductionmentioning
confidence: 99%
“…In order to examine the factor by which too much etching has been generated, we have investigated the relation between energy and the etching mechanism. In the process, side etching was considered as a factor that causes a form error [4]. Figure 3 shows side etching.…”
Section: Introductionmentioning
confidence: 99%
“…Three-dimensional microfabrication technology using Synchrotron Radiation (SR) lithography is possible to be nanoscale and high aspect ratio fabrication which harnessed the characteristic of SR, and fabricate structures which has free-form and sidewall inclination surface. Before now, some research of three-dimension processing methods using SR light is already reported [2] [3] [4] [5] [6]. Each of these is techniques of giving exposure energy distribution to a resist surface.…”
Section: Introductionmentioning
confidence: 99%